Exploring the challenges of LPG cylinders logistics management : Insights from household end users and retailers - Siti Humaira Naqiah, Azmi (2024)
The growing demand for liquefied petroleum gas (LPG) has intensified the complexities of its supply chain, posing significant challenges for both household users and retailers. As a vital energy source, the efficient management of LPG cylinder returns, supply, and distribution is crucial for ensuring customer satisfaction and operational effectiveness. This study investigates these processes in Seremban, Malaysia, aiming to identify the key challenges faced by stakeholders in the LPG sector. The research seeks to understand the operational difficulties in managing LPG cylinders and how these issues impact customer experiences and overall supply chain efficiency. The primary objectives are to explore the specific challenges encountered by household users and retailers in the returns, supply, and distribution of LPG cylinders. A qualitative research design was employed, utilizing semi-structured interviews with 14 participants, including both household users and retailers, to gain detailed insights into their experiences. Findings indicate that household users face issues with the limited availability of delivery services and high costs associated with emergency deliveries. Retailers, on the other hand, struggle with inventory management and ensuring customer satisfaction. The study highlights the interconnected nature of these challenges, emphasizing the need for enhanced communication and collaboration within the supply chain. In conclusion, the research underscores the need for strategic improvements in the LPG distribution system to boost operational performance and customer satisfaction. Recommendations include adopting more flexible delivery options, implementing transparent pricing strategies, and fostering better collaboration among stakeholders to optimize the supply chain. By addressing these challenges, the LPG industry can create a more sustainable and user-friendly market, benefiting both household users and retailers and contributing to a more efficient and effective LPG supply chain